Personal and organizational correlates of burnout among teachers of selected schools in the Diocese of Cubao - Llanos, Maria Elena T. (2006)
The main purpose of this study was to find out the personal and organizational correlates of burnout among teachers of selected schools in the Diocese of Cubao. The researcher utilized the descriptive method using the Maslach Burnout Inventory-Education Survey by Cristina Maslach and Jackson, Personal Factor Sheet, Job Satisfaction Survey by Spector, and Teacher Support Questionnaire by Hoy. These questionnaires were distributed to 161 Basic Education teachers in Cubao. Findings showed the respondents' level of burnout for each of the three dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. Teacher support is significantly related to all the levels of burnout.